Childhood Tuberculosis: Epidemiology, Diagnosis, Treatment, and Vaccination - Kuo-Sheng Tsai; Hsiao-Ling Chang; Shun-Tien Chien; Kwo-Liang Chen; Kou-Huang Chen; Ming-Hsin Mai; Kow-Tong Chen (Pediatrics and Neonatology)
Despite the existence of a government-run tuberculosis (TB) control program, the current nationwide burden of TB continues to be a public health problem in Taiwan. Intense current and previous efforts into diagnostic, therapeutic, and preventive interventions have focused on TB in adults, but childhood TB has been relatively neglected. Children are particularly vulnerable to severe disease and death following infection, and children with latent infections become reservoirs for future transmission following disease reactivation in adulthood, thus fueling future epidemics. Additional research, understanding, and prevention of childhood TB are urgently needed. This review assesses the epidemiology, diagnosis, treatment, and relevant principles of TB vaccine development and presents efficacy data for the currently licensed vaccines.